Organophosphorus flame retardants and persistent, bioaccumulative, and toxic contaminants in Arctic seawaters: On-board passive sampling coupled with target and non-target analysis. (October 2019) - Gao, Xiaozhong; Huang, Peng; Huang, Qinghui; Rao, Kaifeng; Lu, Zhibo; Xu, Yiping; Gabrielsen, Geir Wing; Hallanger, Ingeborg; Ma, Mei; Wang, Zijian
Abstract: Organic pollutants in the Arctic seas have been of concern to many researchers; however, the vast dynamic marine water poses challenges to their comprehensive monitoring within appropriate spatial and temporal scales in the Arctic. In this study, on-board passive sampling of organic pollutants using a self-developed device coupled with triolein-embedded cellulose acetate membranes (TECAMs) was performed during an Arctic cruise. The TECAM extracts were used for target analysis of organophosphorus flame retardants (PFRs), and non-target screening of persistent, bioaccumulative, and toxic (PBT) contaminants using two-dimensional gas chromatography with time-of-flight mass spectrometry (GC × GC-TOFMS). Sixteen chemicals were screened out as PBT contaminants from the 1500 features in the non-target analysis and further identified. Consequently, two chlorinated PFRs (tris(chloroisopropyl)phosphate and tris(1, 3-dichloroisopropyl)phosphate) and four PBT contaminants (4- tert -butylphenol, 2-isopropylnaphthalene, 1, 1, 3-trimethyl-3-phenylindane, and 1-phenylnonan-1-one) were accurately quantified, with the temporally and spatially integrated concentrations ranging from 0.83 ng L −1 to 20.82 ng L −1 in the seawaters. Sources and transport of the contaminants were studied, and ocean current transport (West Spitsbergen Current, WSC) and local sources (human settlement, Arctic oil exploitation, and petroleum fuel emissions) were found to contribute to the presence of the different contaminants. Finally, annual transport fluxes of the contaminants from the North Atlantic to the Arctic Ocean by WSC were estimated, and the results indicate that their hazard to the Arctic should be concerned. Graphical abstract: Image 1 Highlights: On-board passive sampling was performed with self-developed device in Arctic seas. Non-target screening resulted in the discovery of four PBT contaminants. Temporally and spatially integrated concentrations were estimated. Ocean current transport and local sources contributed to Arctic organic pollution. Annual transport fluxes of contaminants by West Spitsbergen Current were estimated. Abstract : Capsule: Source and transport of PFRs and PBT contaminants in Arctic seas were studied by on-board passive sampling coupled with target and non-target analysis.